2004
DOI: 10.1093/aje/kwh149
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Circumcision Status by Adolescents

Abstract: In epidemiologic studies of the relation between circumcision and sexually transmitted infections, it is necessary to rely on self-report of circumcision status. The purpose of this 2002 study in Houston, Texas, was to determine whether adolescent males could make correct self-reports. During physical examinations, adolescents were asked whether they were circumcised. The authors then examined the adolescents' genitalia. Circumcision status was recorded as complete (glans penis fully exposed), partial (glans p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 9 publications
3
40
3
Order By: Relevance
“…A study of the validity of a self-report of circumcision status among adolescent males demonstrated high sensitivity (91%) and high specificity (95%) among those who knew their circumcision status. 22 In that study of largely Black and Hispanic boys, 27% did not know their circumcision status, whereas in our study only 0.1% did not know their status, perhaps reflecting our predominantly adult sample. We therefore consider substantial misclassification unlikely.…”
Section: Discussioncontrasting
confidence: 65%
“…A study of the validity of a self-report of circumcision status among adolescent males demonstrated high sensitivity (91%) and high specificity (95%) among those who knew their circumcision status. 22 In that study of largely Black and Hispanic boys, 27% did not know their circumcision status, whereas in our study only 0.1% did not know their status, perhaps reflecting our predominantly adult sample. We therefore consider substantial misclassification unlikely.…”
Section: Discussioncontrasting
confidence: 65%
“…7,8 These findings underscore the necessity of using a standardized clinical examination for establishing circumcision status for the purpose of research on circumcision. It also highlights the potential difficulty of advising on care of the circumcised and uncircumcised penis when an individual and/or clinician may not know which condition is present.…”
Section: Nhanesmentioning
confidence: 90%
“…It should be noted that circumcision status may be subject to misclassification. In a study of adolescents¸ only 69% of circumcised and 65% of uncircumcised young men correctly identified their circumcision s tatus as verified by physical exam [68].…”
Section: Status Of Male Circumcision In the Usamentioning
confidence: 92%